SISTEM USAHA TANI TERPADU DI LAHAN LEBAK KABUPATEN HULU SUNGAI SELATAN, KALIMANTAN SELATAN - Qomariah, Retna; Amalie, Noor; Rina, Yanti (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Integrated Farming System on Fresh Water Swampy Land in Hulu Sungai Selatan Regency, South Kalimantan. The utilization of fresh water swampy land has not been optimal due to some land bio-physical and socio-economical constraints so that the production and income of the farmers are still low. In order to increase the farmers, an integrated farming system of specific location suitable with the bio-physical and socioÂeconomical conditions of farmers is needed. Research on Farming System in Fresh Swampy Land in Hulu Sungai Selatan Regency is aimed to obtain a model of integrated farming system which can be adopted by the farmers, give benefits and increase the farmer income continually. The farming system models consisted of three models (MI, M2, and M3) conducted by 25 cooperator farmers with the total area of Â± 10 ha and seven cooperators were chosen to carry out duck husbandry (feed fermentation technology) at their yards. One hundred and seventy five (175) ducks were used in the research. For the standard of comparison/ non-cooperator, fifteen farmers were selected from around the research area (Hamayung Utara Village). The data were collected by using farm record keeping method (FRK) and survey. The collected data were analyzed by using ratio of revenue and cost (R/C) and MBCR approaches. The research results show that integrated farming models could be adopted by farmers, were beneficial and increased farmer incomes and were feasible to be developed with a pattern of rice + corn + chili in the rice field and duck husbandry in the yard with MBCR value of 9.69, a net income of Rp 6,307,097 per 0.334 ha, 37.7% higher than the net income of model farmers which was Rp.4,586,893. The net income of the introduced model in 2005 compared to that model farmers increased 144%, i.e. from Rp.1,.740,476 to Rp.4,246,946 per 0.97 ha. Key words: Farming system, fresh water swampy landPemanfaatan lahan lebak masih belum optimal karena berbagai kendala biofisik lahan dan sosial ekonomi sehingga produksi dan pendapatan petani rendah. Untuk meningkatkan pendapatan petani diperlukan model sistem usahatani terpadu yang spesifik lokasi sesuai dengan kondisi biofisik dan sosial ekonomi petani. Pengkajian Sistem Usahatani di Lahan Lebak Kabupaten Hulu Sungai Selatan bertujuan untuk mendapatkan model usahatani terpadu yang dapat diadopsi petani, menguntungkan dan meningkatkan pendapatan petani secara berkelanjutan. Model sistem usahatani yang dikaji terdiri dari tiga model sistem usahatani (Ml, M2, dan M3) yang dilakukan oleh 25 orang petani kooperator dengan luas areal Â± 10 ha dan dipilih 7 orang kooperator untuk melaksanakan usahatani itik (teknologi pakan fermentasi) di lahan pekarangan. Jumlah itik yang digunakan dalam pengkajian sebanyak 175 ekor. Sebagai pembanding/non kooperator dipilih 15 orang petani yang ada di sekitar wilayah pengkajian (Desa Hamayung Utara) secara acak. Data dikumpulkan melalui farm record keeping dan survei. Data yang terkumpul dianalisis menggunakan pendekatan imbangan biaya dan pendapatan (R/C) dan MBCR. Hasil pengkajian menunjukkan model usahatani terpadu dapat diadopsi petani, menguntungkan dan meningkatkan pendapatan serta layak untuk dikembangkan dengan pola usahatani padi + jagung + cabai di lahan sawah dan ternak itik di lahan pekarangan, dengan nilai MBCR = 0,69, pendapatan bersih sebesar Rp.6.307.097 per 0,334 ha, lebih tinggi sebesar 37,5% dibanding pendapatan bersih model petani sebesar Rp.4.586.893.Pendapatan bersih model introduksi tahun 2005 dibanding dengan pendapatan bersih model petani meningkat sebesar 144% yaitu dari Rp.1.740.476 menjadi Rp.4.246.946 per luas 0,397 ha.Kata kunci: Sistem usahatani terpadu, lahan lebak,Kalimantan Selatan